June 30 MEMORANDUM O'Connor Urb Resources Inc SUB CT June Advity Report (Tufts Archival Research Center, 2007)
Activity report for the month of June. Discusses the actions of Urban Resources Inc. with regard to cigarette taxes, clean indoor air and workplace smoking legislation in the northeast.